Edge Trimming Analysis for Surface Quality of Hybrid Composite - CFRP/Al2024 - Saiful Bahri, Mohamed; Ismail, J; Mohamad, M; Mohamad, W.N.F.; Mohamed, A.S; Mohd, A (2017)
The application of hybrid composite materials has increased due to their strength and light weight ratio. Edge trimming of these materials was extremely difficult due to the anisotropic and non-homogeneous structures of CFRP and ductile nature of aluminium. This research was focused on edge trimming process via down milling operation. Three cutting parameters were examined namely spindle speed, feed rate and depth of cut. The extension of two level full factorial design, Centre Composite Design (CCD) was used to plan systematic experimental methodology. The analysis of the influence and the interaction factors associated to surface quality was studied. The objective was to obtain machined surface quality of CFRP/Al2024 between 0.4 µm to 0.6 µm. The depth of cut was the most significant factor for Al2014 and meanwhile the spindle speed and feed rate were significant factors of CFRP. The validation experiment was conducted at optimum level of recommendation control factors setting to compare the deviation of predicted value from actual/measured value. Surface roughness of CFRP was found to be at 0.594 micron at the setting of spindle speed, 11750 rpm, feed rate, 750 mm/min and depth of cut, 0.255 mm. For Al2024, the surface roughness was found to be at 0.32 micron.